PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELUAN PADA PRODUK UD. YULI MAKMUR DI DESA SEMIRING KABUPATEN SITUBONDO DENGA MINAT BELI SEBAGAI VARIABEL INTERVENING - Qomariyah, Umam Durrotul; Wahyuni, Ika; Syahputra, Hendra (Fakultas Ekonomi dan Bisnis, 2025)
This study aims to understand how product quality, price, and promotion influence consumers' purchasing decisions for local snack products, with a particular focus on the mediating role of purchase intention in linking these factors to the final buying decision. The background of this study arises from the increasingly intense competition in the snack food industry, particularly for micro-enterprises such as UD. Yuli Makmur, which face challenges in maintaining product quality, setting competitive prices, and developing effective promotional strategies. This research employs a quantitative method with a descriptive approach, utilizing observation, interviews, literature review, and the distribution of questionnaires to consumers. The results of the study indicate that consumers consider multiple aspects simultaneously before making a purchase decision; consistent quality, value-for-money pricing, and effective promotion are proven to influence both purchase intention and actual buying decisions. Purchase intention plays a crucial role in bridging consumers’ initial perceptions of the product to their final purchasing decision. These findings offer practical contributions for business practitioners in formulating more targeted marketing strategies and serve as an academic reference for understanding consumer behavior, particularly within the small business sector striving to enhance competitiveness and sustain customer loyalty.